An early glance into smartphone dependence in a rural LMIC and relationships with mindfulness and depressive symptoms - Pang, Nicholas Tze Ping; Mathias Wen Leh Tseu; Gloria Pei Ying Lee; Helda Artika Honey; Jane Ivana Joss; Mohd Amiruddin Mohd Kassim; Min Kwon (Primrose Hall Publishing Group, 2020)
A rising issue in the child and adolescent global mental health pandemic is smartphone addiction. However, most evidence has come from urbanised countries in the developed world or university undergraduate students in LAMICs. This study aims to ascertain core psychometric properties of a previously unvalidated brief smartphone addiction scale for adolescents, determine gender-based prevalence of smartphone addiction in adolescents in rural areas, and assess relationships with concurrent measures of a state of mindfulness and depression. Secondary data from a health screening in a Dusun-speaking village in rural Borneo was analysed, with respondents filling in sociodemographic questionnaires and three Malay-language scales: MAAS, PHQ-9, and SAS-SV, which measure the state of mindfulness, depression, and smartphone addiction respectively. The SAS-SV-M exhibited satisfactory internal consistency and was consistent with a uni factorial model in the original paper. There were significant gender differences for smartphone addiction, but no significant difference between all 3 measured variables for age. Significant inverse correlations existed between mindfulness and depression, but not with neither and smartphone addiction, with these correlations persistent upon multiple regression. This study pioneeringly establishes prevalence by gender for smartphone addiction in a rural LAMIC setting, and concurs with extant findings that mindfulness and depression are inversely correlated.